2016
DOI: 10.1523/jneurosci.3212-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cognitive Dysfunction after Traumatic Brain Injury Is Improved with a Phosphodiesterase 4B Inhibitor

Abstract: Learning and memory impairments are common in traumatic brain injury (TBI) survivors. However, there are no effective treatments to improve TBI-induced learning and memory impairments. TBI results in decreased cAMP signaling and reduced cAMP-response-element binding protein (CREB) activation, a critical pathway involved in learning and memory. TBI also acutely upregulates phosphodiesterase 4B2 (PDE4B2), which terminates cAMP signaling by hydrolyzing cAMP. We hypothesized that a subtype-selective PDE4B inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 69 publications
9
52
2
Order By: Relevance
“…Furthermore, A33 levels were nearly 2-fold higher in the injured brain than in the uninjured. The increased distribution of A33 in the acutely injured brain are contrary to what was previously observed in chronic A33-treated animals, where there was no significant difference in brain A33 levels in sham versus TBI animals [50]. The increased levels of A33 in the injured brain are likely due to blood-brain barrier (BBB) breakdown at this early time point after TBI [71].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, A33 levels were nearly 2-fold higher in the injured brain than in the uninjured. The increased distribution of A33 in the acutely injured brain are contrary to what was previously observed in chronic A33-treated animals, where there was no significant difference in brain A33 levels in sham versus TBI animals [50]. The increased levels of A33 in the injured brain are likely due to blood-brain barrier (BBB) breakdown at this early time point after TBI [71].…”
Section: Discussionmentioning
confidence: 90%
“…A33 has a half-life of approximately 3.8–4.5 hrs in the mouse brain, and is over 50-fold more selective for PDE4B (IC 50 = 27 nM) over PDE4D (IC 50 = 1569 nM) and other PDEs (IC 50 > 10μM) [49, 50]. This selectivity is due to a single amino acid polymorphism in the C-terminus of PDE4B, termed CR3 (Control Region 3) [49, 51].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that PDE4 inhibition at 2 weeks (Titus et al, 2013b) and 3 months (Titus et al, 2016) post-FPI improved both LTP in vitro and cognition in vivo . This contrasts with our observation that delayed PDE4 inhibition (23 h post-injury) did not prevent blast-induced LTP deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative PDE4 inhibitors (piclamilast, ibudilast) similarly preserved plasticity. Although no other study has investigated the therapeutic potential of PDE4 inhibition after blast, several studies have observed that PDE4 inhibition preserved LTP measured 2 weeks and 12 weeks following FPI in rats (Titus et al, 2013b; Titus et al, 2016). The effectiveness of either ibudilast or piclamilast following TBI is unknown; however, ibudilast prevented LTP-deficits in cortical cell cultures after microglia activation (Mizuno et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PDE4 subtypes, PDE4D is considered to be related to cognitive improvement [34,35] while PDE4B is also considered to be involved in the cognitive function [36]. It would be worth investigating in future the relationship among treatment with roflumilast, PDE4 occupancy, and effects on cognitive domains in preclinical and clinical settings.…”
Section: Discussionmentioning
confidence: 99%